Autonomous Non Antioxidant Roles for Fasciola hepatica Secreted Thioredoxin-1 and Peroxiredoxin-1 - Dorey, Amber; Cwiklinski, Krystyna; Rooney, James; De Marco Verissimo, Carolina; López Corrales, Jesús; Jewhurst, Heather; Fazekas, Barbara; Calvani, Nichola Eliza Davies; Hamon, Siobhán; Gaughan, Siobhán; Dalton, John P.; Lalor, Richard (Frontiers in Cellular and Infection Microbiology, 2021)
Trematode parasites of the genus Fasciola are the cause of liver fluke disease (fasciolosis) in humans and their livestock. Infection of the host involves invasion through the intestinal wall followed by migration in the liver that results in extensive damage, before the parasite settles as a mature egg-laying adult in the bile ducts. Genomic and transcriptomic studies revealed that increased metabolic stress during the rapid growth and development of F. hepatica is balanced with the up-regulation of the thiol-independent antioxidant system. In this cascade system thioredoxin/glutathione reductase (TGR) reduces thioredoxin (Trx), which then reduces and activates peroxiredoxin (Prx), whose major function is to protect cells against the damaging hydrogen peroxide free radicals. F. hepatica expresses a single TGR, three Trx and three Prx genes; however, the transcriptional expression of Trx1 and Prx1 far out-weighs (>50-fold) other members of their family, and both are major components of the parasite secretome. While Prx1 possesses a leader signal peptide that directs its secretion through the classical pathway and explains why this enzyme is found freely soluble in the secretome, Trx1 lacks a leader peptide and is secreted via an alternative pathway that packages the majority of this enzyme into extracellular vesicles (EVs). Here we propose that F. hepatica Prx1 and Trx1 do not function as part of the parasite’s stress-inducible thiol-dependant cascade, but play autonomous roles in defence against the general anti-pathogen oxidative burst by innate immune cells, in the modulation of host immune responses and regulation of inflammation.